Combining cationic liposomal delivery with MPL-TDM for cysteine protease cocktail vaccination against Leishmania donovani: evidence for antigen synergy and protection. - Amrita Das; Nahid Ali (Public Library of Science (PLoS), 2014)
BACKGROUND:With the paucity of new drugs and HIV co-infection, vaccination remains an unmet research priority to combat visceral leishmaniasis (VL) requiring strong cellular immunity. Protein vaccination often suffers from low immunogenicity and poor generation of memory T cells for long-lasting protection. Cysteine proteases (CPs) are immunogenic proteins and key mediators of cellular functions in Leishmania. Here, we evaluated the vaccine efficacies of CPs against VL, using cationic liposomes with Toll like receptor agonists for stimulating host immunity against L. donovani in a hamster model. METHODOLOGY/PRINCIPAL FINDINGS:Recombinant CPs type I (cpb), II (cpa) and III (cpc) of L. donovani were tested singly and in combination as a triple antigen cocktail for antileishmanial vaccination in hamsters. We found the antigens to be highly immunoreactive and persistent anti-CPA, anti-CPB and anti-CPC antibodies were detected in VL patients even after cure. The liposome-entrapped CPs with monophosphoryl lipid A-Trehalose dicorynomycolate (MPL-TDM) induced significantly high nitric oxide (up to 4 fold higher than controls) mediated antileishmanial activity in vitro, and resulted in strong in vivo protection. Among the three CPs, CPC emerged as the most potent vaccine candidate in combating the disease. Interestingly, a synergistic increase in protection was observed with liposomal CPA, CPB and CPC antigenic cocktail which reduced the organ parasite burden by 1013-1016 folds, and increased the disease-free survival of >80% animals at least up to 6 months post infection. Robust secretion of IFN-γ and IL-12, along with concomitant downregulation of Th2 cytokines, was observed in cocktail vaccinates, even after 3 months post infection. CONCLUSION/SIGNIFICANCE:The present study is the first report of a comparative efficacy of leishmanial CPs and their cocktail using liposomal formulation with MPL-TDM against L. donovani. The level of protection attained has not been reported for any other subcutaneous single or polyprotein vaccination against VL.